Detection of Artificial Intelligence in Scientific Writing: Turnitin vs. ChatGPT - Wilches-Visbal, Jorge Homero; Pérez-Anaya, Oskarly; Campo-Arias, Adalberto (Revista Cubana de Información en Ciencias de la Salud, 2024)
Artificial intelligence can be defined, with some skepticism or controversy, as a set of algorithms in a computer program to develop conceptual models, computational model rewrites, programming language adjustments and designs, and physical machinery, among other processes that allow humanity to perform more efficiently and thoroughly, activities that eventually require a certain cognitive rigor and scientific techniques. However, AI development, application, and manipulation are limited to a small group of individuals with resources or knowledge. Given the advancement of AI, the need to introduce ethical or bioethical aspects of this and other new technologies into the curricula arises in parallel in schools and academic computer science programs. For López Baroni, (2019), the discussion must not revolve around bioethics, which implies that the entities or systems that intervened must be alive, such as humans, animals, or genetically modified organisms, excluding robots. A dominant element that feeds AI is Big Data, which comprises vast amounts of data ranging from human preferences to weather, sports, and history, among others, to predict future events as reliably as possible4. AI assumes that the more data can have and processed, the more opportunity authors have to anticipate the prediction of a particular event or behavior(4). The fear of AI is not necessarily related to the fact that these types of systems resemble human abilities such as thinking, reasoning, or replicating in some way characteristics and cognitive abilities of this species, but rather to the inappropriate use that they can give it. Some people, or failing that, to the fact that the AI itself becomes a risk to the extent that it does not develop a conscience or ethics like the human.